2019
DOI: 10.4103/ija.ija_724_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of aprepitant and ondansetron for the prevention of postoperative nausea and vomiting (PONV): A double blinded, randomised control trial in patients undergoing breast and thyroid surgeries

Abstract: Background and Aims: Aprepitant, a Neurokinin-1 receptor antagonist, has been evaluated in abdominal and neurosurgeries, but its effect is less clear in breast and thyroid surgeries, which are also known to be high risk for post-operative nausea and vomiting (PONV). This study was done to compare the antiemetic efficacy of ondansetron and aprepitant in women undergoing mastectomy and thyroidectomy. Methods: One hundred and twenty-five ASA I and II, female patients, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Among patients in a randomized study ( N = 60) who underwent cholecystectomy, oral aprepitant 80 mg given 3 h before anesthesia was superior to ondansetron 4 mg for nausea control at 6 h following surgery; however, nausea control between the groups was similar 24 h following surgery 39 . Other randomized, double‐blind studies reported similar efficacy with oral aprepitant 40 mg versus intravenous palonosetron 0.075 mg in women at high risk for PONV undergoing gynecologic surgery 40 and with aprepitant 40 mg versus ondansetron 8 mg in high‐risk women who underwent a mastectomy or thyroidectomy 41 …”
Section: Efficacy Of Nk1ras Investigated For Ponv Prophylaxismentioning
confidence: 86%
See 1 more Smart Citation
“…Among patients in a randomized study ( N = 60) who underwent cholecystectomy, oral aprepitant 80 mg given 3 h before anesthesia was superior to ondansetron 4 mg for nausea control at 6 h following surgery; however, nausea control between the groups was similar 24 h following surgery 39 . Other randomized, double‐blind studies reported similar efficacy with oral aprepitant 40 mg versus intravenous palonosetron 0.075 mg in women at high risk for PONV undergoing gynecologic surgery 40 and with aprepitant 40 mg versus ondansetron 8 mg in high‐risk women who underwent a mastectomy or thyroidectomy 41 …”
Section: Efficacy Of Nk1ras Investigated For Ponv Prophylaxismentioning
confidence: 86%
“…39 Other randomized, double-blind studies reported similar efficacy with oral aprepitant 40 mg versus intravenous palonosetron 0.075 mg in women at high risk for PONV undergoing gynecologic surgery 40 and with aprepitant 40 mg versus ondansetron 8 mg in high-risk women who underwent a mastectomy or thyroidectomy. 41 Clinical investigations of aprepitant in two-drug combinations have demonstrated efficacy in PONV prophylaxis, particularly with aprepitant combined with dexamethasone and aprepitant combined with ondansetron (Table 3). In 2011, in a randomized, double-blind study (N = 104) in patients undergoing a craniotomy, Habib and colleagues demonstrated that oral aprepitant 40 mg administered 1-3 h before anesthesia combined with intravenous dexamethasone 10 mg, compared with intravenous ondansetron 4 mg combined with dexamethasone 10 mg, significantly decreased the cumulative incidence of vomiting 48 h after surgery (16% vs. 38%; p = 0.01) and the incidence of vomiting 0-2 h after surgery (6% vs. 21%; p = 0.03) and 0-24 h after surgery (14% vs. 36%; p = 0.01).…”
Section: Aprepitant (Oral Emend)mentioning
confidence: 99%
“…7,11,[20][21][22][23][24][25] In human medicine, PONV affects 20% to 40% of surgical patients overall, and up to 80% of high-risk patients (eg, women, nonsmokers, those with a previous history of PONV or motion sickness, and those receiving opioids). 6,8,26,27 Numerous human studies 7,[21][22][23]25 have demonstrated that NK-1 receptor antagonists are effective in the prevention and treatment of postoperative nausea and superior to other antiemetics in the prevention and treatment of postoperative vomiting. Due to its favorable efficacy profile and superiority, treatment with an NK-1 receptor antagonist has been recommended for human patients at risk for PONV and for whom PONV may cause serious adverse outcomes, such as aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…[1] As one of the most common postoperative adverse reactions, reported to be even more unbearable than pain, PONV not only increases the risk of postoperative complications but also brings discomfort to patients, reduces patient satisfaction, and prolongs hospital stays. [2][3][4] It is also one of the main reasons for unplanned readmission, leading to a great burden on patients. [5,6] The incidence of PONV is approximately 30% among the general population and 80% among the high-risk population, with an Apfel risk score of 3 or 4.…”
Section: Introductionmentioning
confidence: 99%
“…Although an increasing number of studies on the use of aprepitant in clinical practice have been reported in recent years, its effectiveness in preventing PONV remains unclear. [4,[12][13][14][15] We conducted a meta-analysis of randomized controlled trials (RCTs) to understand better how aprepitant use affects current PONV management strategies with a view to improving patient postoperative comfort.…”
Section: Introductionmentioning
confidence: 99%